Amyloid β perturbs elevated heme flux induced with neuronal development - Chantal Vidal; Kelly Daescu; Keely E. Fitzgerald; Anna Starokadomska; Ilya Bezprozvanny; Li Zhang (Alzheimer’s & Dementia: Translational Research & Clinical Interventions, 2019)
Abstract Introduction Heme is a central molecule in mitochondrial respiration and ATP generation in neuronal cells. Thus, we assessed the importance of altered heme metabolism in Alzheimer's disease (AD) pathogenesis. Methods To investigate the role of altered heme metabolism in AD, we identified heme‐related proteins whose expression is altered in AD patients and mouse models exhibiting amyloid pathology. We detected the levels of proteins involved in heme synthesis, uptake, degradation, and function during neuronal differentiation and characterized the effects of Aβ. Results We found that the expression levels of the rate‐limiting heme synthetic enzyme ALAS1 and heme degradation enzyme HO‐2 are selectively decreased in AD patients and mice. Aβ selectively reduces the levels of HO‐2 and heme degradation, which are elevated to support neuronal functions in fully differentiated neuronal cells. Discussion Our data show that lowered heme metabolism, particularly the decreased levels of heme degradation and HO‐2, is likely a very early event in AD pathogenesis.